Developing Animals : Wildlife and Early American Photography - Brower, Matthew, 1971- (Book collections on Project MUSE., 2011)
Pictures of animals are now ubiquitous, but the ability to capture animals on film was a significant challenge in the early era of photography. In Developing Animals, Matthew Brower takes us back to the time when Americans started taking pictures of the animal kingdom, at the beginning of the twentieth century, the moment when photography became a mass medium and wildlife photography an increasingly popular genre. Developing Animals compellingly investigates the way photography changed our perception of animals. Brower analyzes how photographers created new ideas about animals as they moved fr.